New Media New World - YENİHAN, BORA; GÜVENÇ, DİLAY; EKŞİ, OYLUM; KONAK, AYŞİN; GÜCENMEZ, TUĞBA; NURDOĞAN, ALİ KEMAL; CEREV, GÖKÇE; TOPKAYA, ÖZGÜR; PEKER, ZAHİDE; KURAN, MELİH; SARIİPEK, DOĞA BAŞAR; KÖSEOĞLU, YAKUP; et al. (Sakarya Üniversitesi Yayınları, 2024)
The world is changing. What is important for today is that the increase in the speed of change in the world has almost become untrackable. Perhaps the most important reason for this speed in question is the new media approach. This rapid change is constantly affecting both individuals and society, and these effects are sometimes positive and sometimes negative. Addressing this change and its effects in a single dimension may not only leave the subject incomplete, but may also bring about a biased perspective. When the subject is approached from this perspective, the different perspectives taken by scientists and researchers working in different disciplines within the scope of the new world and new media add integrity to the subject. The question that needs to be asked at this point should be “How do the new world order and the new media approach affect individuals first and then the social structure?”. The study titled “New Media New World” attempts to answer this question from different perspectives but by paying attention to context and integrity.